A novel high-performance fold I shaped junctionless FinFET. Issue 4 (1st October 2020) - Liu, Xi; Shang, Jingguo; Sun, Xiaotong; Wu, Meile; Jin, Xiaoshi; Lee, Jong-Ho
ABSTRACT: In this article, a novel high-performance fold I shaped junctionless FinFET (FIS JL FinFET) is proposed. Compared to conventional JL FinFETs, the proposed FIS JL FinFET can realise lower off-state leakage current, lower parasitic capacitance while ensuring no degradation of the subthreshold swing. The electrical properties of the FIS JL FinFET have been extensively investigated through comprehensive discussions of the influences resulting from gate geometry engineering.